Human balance control in 3D running based on virtual pivot point concept - Firouzi, V.; Bahrami, F.; Sharbafi, M. A. (Journal of Experimental Biology, 2022)
Balance control is one of the crucial challenges in bipedal locomotion. Humans need to maintain their trunk upright while the body behaves like an inverted pendulum which is inherently unstable. As an alternative, the virtual pivot point (VPP) concept introduced a new virtual pendulum model to the human balance control paradigm by analyzing the ground reaction forces (GRFs) in the body coordinate frame. This paper presents novel VPP-based analyses of the postural stability of human running in 3D space. We demonstrate the relationship between the VPP position and the gait speed. The experimental results suggest different control strategies in frontal and sagittal planes. The GRFs intersect below the center of mass in the sagittal plane and above the center of mass in the frontal plane. These VPP locations are found for the sagittal and frontal planes at all running speeds. We introduced a 3D VPP-based model which can replicate the kinematic and kinetic behavior of human running. The similarity between the experimental and simulation results indicates the ability of the VPP concept to predict human balance control in running and support its applicability for gait assistance.